Ocena vidnosti in nujnosti uporabe izdelkov kot dejavnikov, ki nakazujeta moč vpliva referenčnih skupin na izbiro izdelka in njegove znamke - Mumel, Damijan (Akademija MM, 1998)
In our contribution we present the results of the research, which is derived from the research work done by Bearden and Etzel (1982), where they explain the influence of necessity/non-necessity and visible/private consumption as factors for determining the power of the reference group impact. Bearden and Etzel define the impact of the reference group on (a) the possession of the product and (b) on the selection of the brand. They distinguish four categories: public necessities, public luxuries, private necessities and private luxuries. Despite the importance of this research, its weakness lies in its categorical approach. From the didactic point of view the categorical approach can be better, because it enables better memorising and a clearer insight into the problem. On the other hand, the categorical approach is questionable because the world is not categorical but dimensional in its nature. We believe that the dimensional approach would be a far suitable one. Probably in majority of products the necessity and visibility are scaled middle and so is the reference group's influence on possessing the product and the selection of the brand. The main purpose of our research was: 1. The analysis of the products regarding its visibility and, separately regarding the necessity of the product. 2. The analysis of the products regarding both dimensions simultaneously. 3. By means of the cluster analysis to find out if there are any groups of similar products regarding the visibility and the necessities of the products. In our research we analysed 43 products (we use the concept product in its broadest sense; we include both material and non-material products; a product is every result of the human physical or mental activity). Respondents - 113 female students of the University of Maribor (age 21). Research results: (a) the products sorted according to both dimensions: visibility and the necessity of products; (b) picture/map of 43 products. From the position of the product on the map we can derive conclusion about the impact of the reference group on product and brand; (c) dendrogram - the result of the cluster analysis with which we divided 43 products in 6 clusters - groups of products. The results do not have only a theoretical, but also a practical value. On the basis of the estimation of the visibility and necessity of the product we can, for each product, define the influence of the reference group on choosing the product and product brand. Therefore the result represent a starting point for the decision whether to use or not to use the reference groups as one of the factors in building the strategy for product promotion, distribution and sale. Every research has its limitations. In this research were at least: product selection and respondent selection.
Keywords: izdelki; konkurenčnost; marketing; potrošniki; psihologija potrošnika; trženje